Die Jerusalemse tempelkuItus se huweliksmaatreel versus Christelike waardes - Aarde, Andries van (Verbum et ecclesia, 1997)
The marriage arrangements in the Jerusalem Temple cult in opposition to Christian values. Equal access for everyone to God's grace in an unmediated way is a central aspect of Jesus' presentation of the Kingdom of God. Inclusivity and egalitarity should be regarded as essential aspects of Christian selfunderstanding. This article aims to show how these values stood in opposition to the marriage arrangements in the Jerusalem Temple cult. Marriage strategies during the patriarchal and monarchical periods prior to the first-century Jerusalem Temple cult are also briefly touched upon. In a following up article the author will argue that Paul's use of the notion "adopted as children of God" should be seen as an expression of the Christian values advocated within an inclusive and egalitarian community.